2001
DOI: 10.1890/1051-0761(2001)011[1602:etroev]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Risks of Engineered Viruses: Modeling Pathogen Competition

Abstract: Recently there has been a great deal of interest in the potential use of genetically engineered baculoviruses as environmentally benign insecticides. Because baculoviruses often have a significant impact on the population dynamics of their hosts, any effort to assess the environmental impact of releasing engineered viruses must confront the question: Will genetically engineered baculoviruses outcompete wild‐type strains, thereby altering the natural population dynamics of the host? To begin to answer this ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…By introducing these data into a mathematical model of Gypsy Moth-NPV dynamics, Dwyer et al (2002) also showed that this enhanced transmission gave the wild-type virus a significant fitness advantage over the egt-minus virus. This analysis has been extended to examining the potential competition between genetically modified baculoviruses with enhanced speed of kill in general (Dushoff & Dwyer 2001). They concluded that faster-acting viruses were unlikely to become dominant unless the reduction in yield was small.…”
Section: Discussionmentioning
confidence: 99%
“…By introducing these data into a mathematical model of Gypsy Moth-NPV dynamics, Dwyer et al (2002) also showed that this enhanced transmission gave the wild-type virus a significant fitness advantage over the egt-minus virus. This analysis has been extended to examining the potential competition between genetically modified baculoviruses with enhanced speed of kill in general (Dushoff & Dwyer 2001). They concluded that faster-acting viruses were unlikely to become dominant unless the reduction in yield was small.…”
Section: Discussionmentioning
confidence: 99%
“…Thus a faster speed of kill means that virus is released from the host more rapidly, and this creates the potential for earlier secondary transmission of disease and more cycles of virus amplification within the single generation of the host. This has clear implications for increased virus fitness (Dushoff & Dwyer 2001). As predicted, the phenotype of the isolate collected from the non‐persistent M. c. pluviale population at Montague on Galiano Island, did not follow this trend.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical exploration of the dynamics of egt plus and minus viruses indicates that the fitness of viruses lacking the egt gene would be less than that of the parent wild-type (Dwyer et al 2002). Extending this analysis to competition between viruses that differ in speed of kill and transmissibility indicates that the faster killing virus requires relatively high levels of transmission to dominate (Dushoff & Dwyer 2001). However, overwinter survival of virus, about which little is known, is crucial in these simulations.…”
Section: The Egt Genementioning
confidence: 97%